Estágio Profissionalizante realizado na Dragon Force - Futebol Clube do Porto Basquetebol - Joana Filipa Mendes Rosas (2017)
The present report describes the activities developed in the in Dragon Force Basketball project during my vocational internship, integrated in "Mestrado de Gestão Desportiva da Faculdade de Desporto da Universidade do Porto". This is a youth sports training project and it's characterized for its excellency, because beyond the sports training that it offers, it pursues dynamic and playful activities to transmit values of growth, not exclusively as an athlete, but also as a conscientious citizen that can add worth to the society. Furthermore, this project as the support of several transversal departments such as the pedagogical areas of health, nutrition, physiotherapy, among others, highlighting themselves in a national level. In this entity I took on roles of Operational Officer and Team Manager. The present report was structured according to the norms and orientations for a redaction and presentation of dissertations and reports of "Faculdade de Desporto da Universidade do Porto": Introduction, characterizing the internship in general and specifying the goal of the report; Framework of the practice and describing the several contexts in which the same as been developed: literary review, legal context, institutional and functional; Realization of the professional practice, presenting all of the tasks and activities developed during the 2016/2017 season; Reflective conclusion and final synthase. In short, this document is a mirror of the period in which I was given an opportunity to put in practice all of the theoretical knowledges learned and, at the same time, a reflection that allowed me to comprehend the relevance of Sport Management in a more sustained way.